1995
DOI: 10.1097/00004032-199503000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Canine 238Pu Biokinetics/dosimetry model to Human Bioassay Data

Abstract: Associated with the use of 238Pu in thermoelectric power sources for space probes is the potential for human exposure, primarily by inhalation and most likely as 238PuO2. Several models have been developed for assessing the level of intake and predicting the resulting radiation dose following human exposure to 239Pu. However, there are indications that existing models do not adequately describe the disposition and dosimetry of 238Pu following human exposure. In this study, a canine model that accounts for thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…(2003) analysed 238 Pu in tissues of a whole-body donor (USTUR Case 0259) who accidentally inhaled plutonium (predominantly 238 Pu) in the form of a highly insoluble ceramic 238 PuO 2 -molybdenum. Along with six other workers exposed at the same time (Hickman et al., 1995), this donor excreted little or no 238 Pu in his urine for several months. Subsequently, however, and with no further intakes, the urinary excretion of 238 Pu increased.…”
Section: Plutonium (Z = 94)mentioning
confidence: 87%
See 3 more Smart Citations
“…(2003) analysed 238 Pu in tissues of a whole-body donor (USTUR Case 0259) who accidentally inhaled plutonium (predominantly 238 Pu) in the form of a highly insoluble ceramic 238 PuO 2 -molybdenum. Along with six other workers exposed at the same time (Hickman et al., 1995), this donor excreted little or no 238 Pu in his urine for several months. Subsequently, however, and with no further intakes, the urinary excretion of 238 Pu increased.…”
Section: Plutonium (Z = 94)mentioning
confidence: 87%
“…Guilmette et al. (1994) and Hickman et al. (1995) developed the model further, adapted it to humans, and applied it to urinary bioassay data from workers who inhaled 238 Pu aerosols (see below). (777) In some of the studies outlined below, urinary excretion rates that increased with time were observed, indicating that the dissolution rate in the lungs increased with time.…”
Section: Plutonium (Z = 94)mentioning
confidence: 99%
See 2 more Smart Citations
“…The observed excretion could be predicted by starting with an initial lung solubility of 1 X 10 -6 d -1 , increasing gradually to 4 X 10 -3 d -1 . A mechanistic model was developed for non-ceramic plutonium oxides in beagles [9], and was eventually adapted to fit the urinary excretion observed in cases involved in the 1971 incident [10,11]. The ICRP66/67 models were calibrated to fit the excretion and autopsy data of a worker who was exposed to ceramic 238 PuO 2 , but since this was only based on one individual, this modified ICRP model is not broadly applicable [12].…”
Section: Mobility In the Laboratorymentioning
confidence: 99%